HUBUNGAN PENGGUNAAN MEDIA SOSIAL TERHADAP SELF EFIKASI PADA REMAJA PUTRI - Amalina; Utami, Risqi (Universitas Batam, 2025)
Self-efficacy is a person's belief in their ability to master a situation and produce something profitable, teenagers prefer to use social media because they can write anything without feeling awkward and embarrassed according to their mood without fear of being embarrassed by others. The purpose of the study was to determine the relationship between the use of social media and the self-efficacy of young women in Karimun Regency. Quantitative research method, cross-sectional approach, from March to May 2024. Place in Tanjung Balai Karimun. The population in this study were young women in the Tanjung Balai Karimun Health Center Working Area totaling 21,819 people. The sampling technique used was purposive sampling, namely the selection of samples based on certain characteristics or traits related to the characteristics of the population based on the considerations of researchers totaling 90 people. The analysis used the test carried out was chi square with a significant limit <0.05, in this bivariate analysis using a computer program. The results of the study on the use of social media from 90 respondents, the majority of social media use was in the moderate category of 70 respondents with a percentage (77.7%). Self-efficacy of female adolescents. Out of 90 respondents, the majority have moderate category self- efficacy with a percentage (68.8%) of 62 respondents. Conclusion: There is a significant relationship between the use of social media and self-efficacy of female adolescents because the p-value (0.000) <0.05 . Keywords: Social Media, Self Efficacy, Adolescent Girls